Perfil de expressão de microRNAs circulantes em carcinomas de fígado, pâncreas e vias biliares - Bertoni, Natália [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Background: Hepatic-pancreatic-biliary tract (HPB) cancers are aggressive carcinomas with common progenitor cells, suggesting that molecular mechanisms of tumorigenesis can be shared between these tumors. MicroRNAs (miRNAs) are important gene expression regulators and have been identified as biomarkers with clinical application in the diagnosis, prognosis and treatment of patients with cancer. The aim of this study was to identify the expression profile of plasma miRNAs in patients with HPB carcinomas and potential biological processes involved in the carcinogenesis of these tumors. Patients and Methods: Twelve plasma samples were analyzed, 4 of which were obtained from patients with hepatocellular carcinoma, 4 with pancreatic adenocarcinoma and 4 with cholangiocarcinoma, and 10 plasma samples from healthy individuals (reference group). The expression profile of circulating miRNAs was determined using the TaqMan Array Human MicroRNA Cards (card A, v3.0) platform. Prediction analysis of target mRNAs potentially regulated by the identified miRNAs and target miRNAs-mRNAs interaction networks were performed. Results: Among the 42 differentially expressed miRNAs identified in plasma obtained from patients with cancers of the liver, pancreas and biliary ducts, 28 miRNAs (67%) were shared between the three tumor subtypes, being 19 under-expressed and 9 over-expressed. MiRNA target predictions followed by enrichment analysis revealed putative target genes associated with transcription, cell division, organization, differentiation, proliferation and apoptosis. Among the under-expressed miRs are: miRs let-7b-5p and let-7c-5p, predicted to regulate genes associated with cancer, HMGA2 and ZNF516; and miR-660-5p, miR-25-3p and miR-92a-3p, which regulate the HAS3 gene. Interestingly, miRNAs with increased expression (mir-130b-3p, miR-142-5p, miR-148a-3p, miR-152-3p, miR-130a-3p and miR-27b-3p) were predicted to regulate genes involved in cellular development. Among them, miR-142-5p showed the highest number of target genes (19 genes). Conclusion: The identification of miRNAs commonly dysregulated in plasma from patients with HPB carcinomas and not in healthy controls suggests an association of these alterations with tumorigenesis mechanisms of these carcinomas. In addition, target genes predicted to be regulated by these miRNAs encode important proteins with different cellular processes with an important role in tumorigenesis. Validation studies in a large number of cases may contribute to the development of new diagnostic and therapeutic strategies for patients with HPB carcinomas.

Introdução: Os carcinomas hepato-pancreato-biliares (HPB) são carcinomas agressivos, com células progenitoras comuns, sugerindo que mecanismos moleculares de tumorigênese podem ser compartilhados entre estes tumores. Os microRNAs (miRNAs) são importantes reguladores da expressão gênica e têm sido investigados como potenciais biomarcadores diagnósticos, prognósticos e de resposta a tratamento de pacientes com câncer. O objetivo deste estudo foi identificar o perfil de expressão de miRNAs no plasma de pacientes com carcinomas HPB e potenciais processos biológicos envolvidos na tumorigênese destes carcinomas. Pacientes e Métodos: Foram analisadas 12 amostras de plasma, sendo 4 obtidas de pacientes com carcinoma hepatocelular, 4 com adenocarcinoma de pâncreas e 4 com colangiocarcinoma e 10 amostras de plasma de indivíduos saudáveis (grupo de referência). A expressão de miRNAs plasmáticos foi determinada por meio do ensaio TaqMan® Array Human MicroRNA Cards (card A, v3.0). Análises de predição de mRNAs-alvo potencialmente regulados pelos miRNAs identificados e redes de interação miRNAs-mRNAs-alvo foram geradas. Resultados: Dos 42 miRNAs com expressão desregulada no plasma de pacientes com carcinomas HPB comparados ao grupo de indivíduos saudáveis, 28 miRNAs (67%) são compartilhados entre os três subtipos tumorais, sendo: 19 com expressão diminuída e 9 com expressão aumentada. Os mRNAs-alvo preditos dos miRNAs com expressão alterada nos carcinomas HPB estão associados com importantes processos, como transcrição, divisão celular, organização, diferenciação, proliferação e apoptose. Dentre os miRs com expressão diminuída destacam-se: let-7b-5p e let-7c-5p, preditos para regular genes associados com câncer, HMGA2 e ZNF516; além dos miRNAs miR-660-5p, miR-25-3p e miR-92a-3p, que regulam o gene HAS3. Interessantemente, os miRNAs com expressão aumentada (mir-130b-3p, miR-142-5p, miR-148a-3p, miR-152-3p, miR-130a-3p e miR-27b-3p) foram identificados como potenciais reguladores de genes envolvidos em processos biológicos de desenvolvimento celular. Dentre eles, o miR-142-5p mostrou o maior número de genes alvos preditos (19 genes). Conclusão: A identificação de miRNAs desregulados no plasma de pacientes com os três subtipos tumorais, mas não em indivíduos saudáveis, sugere uma associação dessa desregulação com os mecanismos comuns de tumorigênese nesses carcinomas. Além disso, os genes-alvo preditos a serem regulados por esses miRNAs codificam importantes proteínas associadas com diferentes processos celulares ligados a tumorigênese. Estudos de validação em um número maior de casos podem contribuir para o desenvolvimento de novas estratégias diagnósticas e terapêuticas para pacientes com carcinomas HPB.
Expression profile of circulating microRNAs in hepato-pancreato-biliary carcinomas
Keywords: Adenocarcinoma de pâncreas; Colangiocarcinoma; MiRNA; MicroRNA circulante; Carcinoma hepatocelular